Components in Melanoma Cytoplasm Might Induce Murine BMSCs Transformation and Expression of Melan-A - 麻婧 史俊娟 王建超 刘俊 吴轲 敖启林 刘卓雅 王小丽 刘胜洪 (Journal of Huazhong University of Science and Technology. Medical sciences, 2011)
This study explored the possibility that the components in melanoma cytoplasm induce murine BMSCs transformation and expression of Melan-A by morphologically observing the changes of BMSCs and immunocytochemically detecting Melan-A in the cells after culturing BMSCs in me-dium containing melanoma cytoplasm components （MCC）. MCC of B16 melanoma cells was prepared and BMSCs were cultured and induced by adding the MCC into culture medium. The cells were morphologically observed and Melan-A was immunohistochemically detected to confirm BMSCs transformation. MCC-induced BMSCs underwent morphological changes. A number of melanin granules appeared in the cytoplasm of the cells and some were released into surrounding areas. Several cells that might come from one cell formed a cluster, and their granules, together with those secreted by other induced BMSCs, formed a so-called ＂sphere-formed structure＂. The induced BMSCs expressed Melan-A. We are led to conclude that there might be some factors in the cytoplasm of melanoma cells that might induce BMSCs transformation toward melanogenic cell, or even melanoma.